ICT and Two Categories of R&D in the Innovation Process among Firms in ASEAN Countries Based on Firm-level Survey Data - Masatsugu Tsuji; Yasushi Ueki; Hidenori Shigeno; Teruyuki Bunno; Hiroki Idota (International Telecommunications Society (ITS), 2018)
This paper attempts to analyze the relationship between ICT and R&D in the innovation process. R&D is categorized into two types: R&D and non-R&D. The former is R&D conducted by specific R&D sections or units, whereas the latter is implemented without explicit or formal units. ICT use in this paper consists of two roles: (i) Internal use of ICT which includes ERP, CRM, CAD/CAM, Groupware, and Intra-SNS; and (ii) External use of ICT which consists of B2B e-commerce, B2C e-commerce, EDI, SCM, and Public-SNS. ICT total contains all of these. Research questions are as follows: (i) whether R&D and formal R&D groups have different innovation processes; (ii) what are the factors of production innovation in R&D groups; and (iii) how ICT use affects (i) and (ii). This study is based on mail surveys in five ASEAN economies, such as Vietnam (Hanoi and Ho Chi Minh City), Indonesia, Laos, the Philippines, and Thailand from 2013 to 2014. The total number of valid responses was 1,061. Ordered probit analysis was employed. The significant variables common to both groups are few. In the R&D group, "ICT total" and "Cross-functional team" was significant variables, whereas in non-R&D group, "ISO9000 series" and "HRD program for workers were significant. From the above estimation results, it is clear that ICT use is positively related to innovation in R&D group, indicating ICT more contributed to their innovation.
Keywords: 330; internal use; external use; ordered probit; HDR; learning; QC